Pengaruh Gaya Kepemimpinan Demokratis Terhadap Kinerja Pegawai Melalui Komitmen Organisasional Sebagai Variabel Intervening - Santoso, Budi; ., Chalimah (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyse the effect of democratic leadership style on employee performance with organisational commitment as an intervening variable at Bank Muamalat KC Purwokerto Raya. The democratic leadership style is characterised by the involvement of team members in decision making, which is expected to increase employees' sense of ownership and responsibility for the organisation. High organisational commitment is expected to mediate the relationship between leadership style and employee performance. The research method used in this study is an associative research method with a quantitative approach. This research aims to determine the relationship between the various variables studied through numerical measurement and statistical analysis. The research subjects involved all employees of Bank Muamalat KC Purwokerto Raya with a total of 34 respondents using saturated sampling technique. Data was collected through a Likert scale-based questionnaire distributed via google form which was then processed using the SmartPLS version 4.0 application. Data analysis techniques using Partial Least Square (PLS) through outer model evaluation, inner model, and hypothesis testing. The results concluded that organisational commitment has a positive and insignificant effect on employee performance, democratic leadership style has a positive and significant effect on employee performance, democratic leadership style has a positive and significant effect on organisational commitment, democratic leadership style has no direct effect on employee performance with the mediation of organisational commitment